Efeitos de Faraday e Kerr em estruturas periódicas metálicas: Grafeno na faixa de THz e Ouro-Dielétrico-Bi:YIG na faixa do infravermelho - SANTOS, Carlos Rafael Marques dos (Universidade Federal do Pará, 2018)
Photonics is a research field whose purpose lies in the use of light (photons), rather than electrons (electronics) in the realization of certain functions such as storage, transfer and processing of signals. In this context, it opens the possibility of development and production of devices whose storage capacity surpasses those of electronic devices. To do this, it is necessary to control the photons similarly, to what is done in electronics with the electrons. The control of radiation, in the context of photonics, can be realized through magneto-optical effects, such as the Faraday and Kerr effects. The Faraday effect is used as the basis of operation of devices such as optical isolators, current sensors and others. In turn, the Kerr effect is the basis of the operation of data storage devices (optical magnetic memory). In the present work, magneto-optical effects of Faraday and Kerr, as well as the transmission of electromagnetic radiation are studied in the regions of terahertz and infrared. In the frequency range that corresponds to the THz, the Faraday effect, the Kerr effect and the radiation transmittance are analyzed in periodic structures of graphene with different geometries. The structures analyzed in this work can present RF, for weak magnetic fields (B =1 T, for example), greater than 3_ depending on the choice of geometry that can be circles, squares, squares with small cuts in the corners and ribbons. Faraday rotation in these systems can be explained by a simple circuit model where the introduction of periodicity in the graphene promotes the increase of the system impedance and consequently changes the magneto-optical properties of the system, improving the rotation of Faraday at high frequencies (larger than 8 THz) still with magnetic field values taken as weak. This characteristic can not be obtained in a uniform sheet of graphene, since it is possible to obtain a strong rotation of Faraday at high frequencies with strong magnetic fields (10 T, for example). Additionally, for the three periodic structures it was calculated the Kerr rotation that can reach the value 3.96_ depending on the geometry chosen. For all cases, the maximum frequency of Faraday and Kerr rotations occur for frequencies greater than 7 THz. These results are better than results already published. In the infrared region are studies the effects of Faraday, Kerr, as well as extraordinary optical transmission in a plasmonic hybrid structure composed of four layers. For this, the Faraday rotation is of 7_ and 0.25 of of transmittance For wavelength 945 nm. Additionally, the Kerr effect can reach 23_. These results are better than results already published. In the proposed structure, the improvement of Faraday’s rotation is due to the increase of the Q factor of the resonances in the magneto-optical material layer.